Eksplorasi, Inventarisasi, dan Karakterisasi Plasma Nutfah Durian Kunyit (Durio zibethinus Murr) di Kecamatan Pupuan, Kabupaten Tabanan - ZULKARNAIN, ZULKARNAIN; PRADNYAWATHI, NI LUH MADE; WIJAYA, I KETUT ARSA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.8, No.1, Januari 2019, 2019)
Exploration, Inventorize, and Characterization of Durian Kunyit (Durio zibethinus Murr) Germplasm in Sub-District of Pupuan, Tabanan District This research aimed to explore, inventorize, and characterize durian kunyit (Durio zibethinus Murr) plants in the sub-district of Pupuan. The research covered the exploration of durian kunyit in each village, the inventorize of the dispersal of durian kunyit, and the characterization of durian kunyit. The variables observed were the agronomic characters, morphology characters, and molecular character of durian kunyit. The results showed the discovery of 8 durian kunyit mother trees scattered at an altitude of 370 – 661 meters above sea level. The agronomic character of durian kunyit fruit are small–medium sized, fruit weight 1,1 kg, fruit length 17,3 cm, fruit diameter 15,0 cm, number of seeds 17 per fruit, aryl texture quite soft, watery condition, taste sweet little bitter, the flesh is quite thick, aril is yellow, the aroma is quite strong, not sticky in the hand and the production reaches 200 pieces per tree at the harvest. The morphology characters of durian kunyit were plants aged 10 – 80 years, plant height 16 m, tree circumference 165 cm, petiole length 17,8 mm, petiole width 2,9 mm, length leaf strands 14,2 cm, leaf blade width 4,9 cm. The molecular character of durian kunyit forms 8 specific banding patterns at 350 – 1600 basepair using the PKBT ISSR Primer 2.